Analysis of Information Security in Data Leaks in The PeduliLindungi Application - Sundari Retno Andani (STMIK Budi Darma, 2021)
In the midst of the COVID-19 pandemic, the Indonesian government is trying to control the spread of COVID-19 in various ways, one of which is through the use of technology. The Indonesian government has built and developed a surveillance application called PeduliLindungi to help the government with tracing and tracking to stop the spread of COVID-19. This application requires personal data and utilizes the bluetooth network in location tracking for tracing contact history with COVID-19 sufferers. The search results will make it easier for the government to identify people who are exposed and need further treatment to stop the spread of COVID-19. But besides that, there are many public concerns about the leakage of personal data from the PeduliLindung application. This research focuses on the leakage of personal data and misuse of personal data from the PeduliLindung application from an information security perspective. This study is a study that aims to analyze data security in the PeduliLindung application